Living in Nyanga: an exploratory study on resilience among violence-affected male youth from a community in Cape Town - Dikeni, Viwe (Department of Social Development, 2024)
Violence is prevalent in contemporary South Africa and is considered one of the country's primary challenges. There are many reasons for the skyrocketing levels of violence, all of which can be seen at the individual, familial, and societal levels. Not many studies have considered the resilience of people in violent communities, particularly young people. This study aims to understand the resiliency factors of the youth of Nyanga who are not involved in crime and violence. To achieve this, the objectives were to explore the perceptions of the youth of Nyanga regarding crime in their community, the impact it has on their lives, and their views on resiliency factors that have buffered them against crime and violence. This study uses an exploratory qualitative design to delve into the resilience of youth in violent communities and learn about the various crimes committed. It identifies factors that lead youths to a life of crime and asks what keeps their peers, who do not perpetrate crime and violence, from doing the same. Furthermore, this research looks into the policies and frameworks that impact the youth. A purposive, non-probability sampling technique was used to select the participants from two local youth organisations, the Nyanga Arts Development Centre and IkamvaYouth Nyanga. Qualitative data was gathered through individual semi- structured interviews and a thematic data analysis method was applied. To ensure the trustworthiness of the study, the relevant data verification was also done. The findings of this study confirm that there are many resilient youths in violent communities faced with adversities. The participants were able to engage in the topic thoroughly, sharing their experiences and practical advice that ensured they stayed away from violence. Interpersonal relationships with family and role models in the community were seen as buffers against violence for many of the participants in the study, as they indicated that these support structures gave them perspective and helped them cope with life challenges. The most important recommendation from the study is the need for resources for the community of Nyanga to help fund mentoring programmes for young boys, sporting initiatives to keep them occupied and teach them new skills, and visible community and police patrolling. Such positive inputs will help build and protect the youth and birth resilient youth who can distinguish between what is productive and beneficial to them and others in the community, and what is not. When aiming to understand the phenomenon of youth resilience in violent communities such as the Nyanga township, a holistic approach is of paramount importance when working with the youth. Publishing and addressing the findings and recommendations of this study will aid in promoting resilient and self-sufficient youth, which in turn helps curb the rate of violence in communities such as Nyanga.